The Role of Self-Supporting Extension Agent in Institutional Development of Farmers in Sijunjung Regency and West Pasaman Regency - Hery Bachrizal Tanjung (Department of Crop Science, Faculty of Agriculture, Andalas University, 2020)
The advancement of agriculture sector in one region cannot be separated from the role of agricultural extension in the region. To cover the deficiency of agricultural extension agents, self-supporting extension agents are recruited from farmers or private parties. This study aims to analyze the role of self-supporting instructors in improving farmer institutions and analyze factors related to the role of self-supporting extension agents in improving farmer institutions. This research was a qualitative descriptive study, and it was conducted in West Pasaman and Sijunjung Regency with a sample of 38 people. The results showed that self-supporting instructors play a significant role in improving farmer institutions; this is seen from 78% of self-supporting extension agents have a role in increasing farmer institutions. Factors related to the role of self-supporting extension agents in improving farmer institutions are (1) the age of agents, (2) the number of partners from farmer groups, and (3) the frequency of training attended by self-supporting extension agents. To increase the role of self-extension extension agents in the institutional development of farmers, it is recommended that institutions who manage the agricultural extension recruit self-supporting extension agents from the millennial generation and facilitate self-supporting extension agents to be able to participate in training related to farming in the agent's area of work.